Assessment of shear damaged and NSM CFRP retrofitted reinforced concrete beams based on modal analysis. (15th December 2016) - Prado, Danilo Mascarenhas; Araujo, Ivan Dario Gomez; Haach, Vladimir G.; Carrazedo, Ricardo
Highlights: CFRP laminates increased the load capacity of all tested beams. Pre-cracking and grooving process reduced the natural frequencies of the beams. Strengthening procedure provide small increase of natural frequencies. Among the evaluate methods, the damage index method provide the best results. Vibration-based techniques are promising to assess damages and retrofitting process. Abstract: Near Surface Mounted (NSM) Carbon Fiber Reinforced Polymer (CFRP) has shown to be a very effective technique for shear strengthening of reinforced concrete beams. Previous work showed important strength increases due to application of NSM CFRP in undamaged beams. However, few results were found in the literature to show the effectiveness of the technique for retrofitting damaged beams, especially those subjected to shear. On the other hand, several studies have shown the applicability of damage identification techniques based on modal analysis in different types of structures. No studies were found on the application of such techniques to identify damage generated by shear, which causes a cracking pattern significantly differently from flexural cracking. The purpose of this investigation is therefore to identify damages generated by shear in reinforced concrete beams through modal analysis techniques. In the same way, for retrofitted beams, to verify the changes of dynamic properties during application of NSM CFRP technique. For this purpose, reinforced concrete beams were produced and some of them were subjected to pre-loads corresponding to 40% and 70% of beam strength. These beams were then retrofitted by NSM CFRP to identify experimentally the efficiency of the procedure. Prior and after any phase of damage and retrofitting, modal analysis were performed allowing comparisons of dynamic properties. Comparisons of natural frequencies, vibration modes, Modal Assurance Criterion, Coordinate Modal Assurance Criterion, modal curvatures and damage index allowed damage identification and localization in most cases. However, it was not possible to identify significant changes of dynamic properties when the beams were retrofitted, although the important increases in strength. In light of these results it is believed that the NSM CFRP technique could not improve significantly the stiffness of the structural element while increased their strength.